Linking Personal Competencies With Transformational Leadership Style Evidence From The Construction Industry In Thailand - Limsila, Kedsuda; Ogunlana, Stephen O. (Penerbit Universiti Sains Malaysia, 2008)
This study explored the linkage between personal competencies and leadership behaviours as well as their influences on leadership outcomes and subordinates’ work performance. Personal competencies were measured using the Project Manager Competency Development (PMCD) tool. Leadership behaviours and outcomes were measured using Multifactor Leadership Questionnaire (MLQ). Data was collected from construction projects in Thailand. Findings revealed that leadership outcomes have significant positive relationship with all personal competencies specified in the PMCD framework, every factor in the transformational style and contingent reward factor in the transactional style. Transformational leaders tend to produce high work quality, work quantity, and problem solving creativity from subordinates. Findings further verified that all PMCD personal competencies have significant positive relationship with every factor in the transformational style. It implies that project managers who apply the transformational style and/or have high personal competencies indicated in PMCD framework are likely to generate greater leadership outcomes and work performance on construction projects